Analysis of ATCOs’ performance and workload with 3D radar display in trajectory based operation - Ao, Tianci (2018)
Rapidly increased air traffic volume has led to a more saturated airspace, which creates the desire for better Air Traffic Management system. Significant progress has been made throughout years of research on Trajectory Based Operation to provide solutions for air traffic congestions. To improve Air Traffic Controllers’ workload and performance during control operations, 3D radar display has been developed and considered as an efficient implementation to suit the purpose. In this study, the effects of 3D radar display on ATCOs’ workload and performance will be investigated using human factor evaluation methods and data analysis techniques. Controlled experiments were conducted with current used 2D radar display simulator to compare and conclude the advantages and necessity of implementing 3D radar display in future Air Traffic Management.